The Man Who Could Not Lose - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Man Who Could Not Lose" by Richard Harding Davis is a novel likely written in the early 20th century. This engaging tale captures the whirlwind romance of Champneys Carter and Dolly Ingram, focusing on the themes of love, societal expectations, and the lure of fortune, particularly in the backdrop of horse racing. As they navigate their unexpected marriage and financial struggles, their relationship is tested by the pursuit of wealth and acceptance. The story follows Champ and Dolly, who impulsively marry despite financial instability and the disapproval of Dolly$1 (Bs overbearing mother, Mrs. Ingram. As they struggle to make ends meet, Champ discovers that he has the uncanny ability to predict winning racehorses in his dreams. This newfound luck thrusts him into a world of gambling and fame, elevating their lives momentarily but also drawing the couple into a tumultuous cycle of prosperity and peril. Their journey portrays the tension between romantic ideals and the harsh realities of life, culminating in a gripping climax as Champ's predictions are put to the ultimate test in a highly anticipated race. Ultimately, the couple's bond and resilience are at the heart of this captivating narrative. (This is an automatically generated summary.)s
Release date is 1999-05-01
Produced by Aaron Cannon, and David Widger
Keywords: Fiction; Short stories